Pengaruh Zooxanthellae Karaug Terhadap Kelangsungan Hidup dan Pertumbuhan Kerang Raksasa Kima (Tridacna squamosa) - Ambariyanto, Ambariyanto (Perhimpunan Biologi Indonesia, 2007)
ABSTRACTThe influence of zooxanthellae isolated from corals on the growth and suwivorshipof giant clams. Giant clam known as marine bivalves (Tridacnidae) which live in coralreef. One important aspect of giant clam biology is the existence of zooxanthellae assymbiotic algae which have important role source of energy In hatchery operationalprocedure zooxanthellae were introduced into larvae. Zooxanthellae were isolated fromadult clams. Since clams are also known as endangered species, it is important to findother sources of zooxanthellae. The objective of this research is to investigate the effectof introduction of zooxanthellae which were isolated from different sources on the survivaland growth of giant clams larvae. The results showed that there is no differences on thesurvivorship and growth of giant clams larvae introduced by zooxanthellae isolated fromseveral corals. This result has open a possibility of using corals as source of zooxanthellaeinstead of using giant clams.Key words : zooxanthellae, giant clams, survivorship, growth